Correction: Facile synthesis and isolation of 5-hydroxymethylfurfural from diphenyl sulfoxide. Issue 12 (1st June 2022) - Zhang, Tongtong; Hu, Yaoping; Huai, Liyuan; Gao, Zhijin; Zhang, Jian
Abstract : Correction for 'Facile synthesis and isolation of 5-hydroxymethylfurfural from diphenyl sulfoxide' by Tongtong Zhang et al., Green Chem., 2021, 23, 3241–3245, ; https://doi.org/10.1039/D1GC00302J .